Uma experiência pedagógica de uso de tecnologias no ensino de área e perímetro com estudantes da educação de jovens e adultos (EJA) - Lasmar, Elizabeth Ferreira Terra (2016)
In this work, we conducted and analyzed geometry activities, using technology to cover the area and perimeter content. Technologies combined with teaching methodology of mathematics were used as tools to mediate the teaching-learning process. The activities were tried in two groups of Youth and Adult Education (EJA) of a state school of Minas Gerais. The education proposal was guided by the research question: “In what ways can using technology create an environment where students of EJA can produce meanings for the ideas of area and perimeter?” A teaching sequence, which included the content at issue, exploring the use of information and communication technologies, was developed, consisting of videos, films, photographs, computer, internet and/or computer programs and also rulers, measuring tapes, tape, compasses, protractors and calculators. We highlight the theoretical framework, the use of technology in school and adult education, with a view to teacher training and pedagogical innovation in the teaching-learning process. This study consisted of a qualitative research and case study. The data collected from the observation of lessons, discussions and activities conducted by the students were recorded in a field journal, an instrument that allowed us to systematize the experiences and the results analyzed. The results showed that students immersed in teaching mathematics mediated by technologies and appreciated their life experiences, participating more actively in activities and discussions, disentangling their learning perspectives and fostering a more meaningful learning.